1996
DOI: 10.1177/016235329601900302
|View full text |Cite
|
Sign up to set email alerts
|

Content Acquisition in Problem-Based Learning: Depth versus Breadth in American Studies

Abstract: A continuing barrier to the implementation of curriculum fostering higher order thinking skills is the perception that use of these programs inevitably results in lower levels of content acquisition. This assumption was challenged in the current study, which compared high school students' scores on a multiple-choice standardized test after traditional or experimental instruction. Students in the experimental classroom were instructed by using an approach called problem-based learning where an ill-structured pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 14 publications
4
50
0
3
Order By: Relevance
“…The learning and motivation of the children participating in RTC was documented in another article . We found similar outcomes in our research and observations of children attending RTC as those found in the literature on PBL and PjBL (Capon & Kuhn, 2004;Chang & Barufaldi, 1999;Hmelo, 1994;Hmelo-Silver, 2004;Gallagher & Gallagher, 2013;Gallagher & Stepien, 1996;Gallagher, Stepien, & Rosenthal, 1992;Vernon & Blake, 1993). These outcomes include authentic learning, creativity, autonomy, critical thinking and problem-solving, motivation and engagement, and collaboration (Dole & Bloom, 2011;).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The learning and motivation of the children participating in RTC was documented in another article . We found similar outcomes in our research and observations of children attending RTC as those found in the literature on PBL and PjBL (Capon & Kuhn, 2004;Chang & Barufaldi, 1999;Hmelo, 1994;Hmelo-Silver, 2004;Gallagher & Gallagher, 2013;Gallagher & Stepien, 1996;Gallagher, Stepien, & Rosenthal, 1992;Vernon & Blake, 1993). These outcomes include authentic learning, creativity, autonomy, critical thinking and problem-solving, motivation and engagement, and collaboration (Dole & Bloom, 2011;).…”
Section: Introductionsupporting
confidence: 88%
“…In the current study, we were interested in seeing if comparable effects could be found on their own students when teachers continued to use PBL and PjBL after completing the course and field experience. both increase student motivation and engagement, (3) both increase critical thinking skills and problem solving, and (4) both increase collaboration skills (Capon & Kuhn, 2004;Chang & Barufaldi, 1999;Hmelo, 1994;Hmelo-Silver, 2004;Gallagher & Gallagher, 2013;Gallagher & Stepien, 1996;Gallagher, Stepien, & Rosenthal, 1992;Vernon & Blake, 1993). The present study adds to our knowledge base of these additional benefits of PBL and PjBL.…”
Section: Introductionmentioning
confidence: 57%
“…Each small group must identify what they know already and what they need to know, and then proceed to gather the missing relevant information and resolve the problem. Problem-based learning research addresses the role of the group in achievement and motivation, the effect of a tutored or tutorless group, and breadth versus depth of content acquisition (Gallagher & Stepien, 1996;Gallagher et al, 1992;White, 1996).…”
mentioning
confidence: 99%
“…Yapılan bu çalışmanın da alan yazındaki benzer çalışmalarla paralellik gösterdiği söylenebilir. Akınoğlu ve Özkardeş Tandoğan (2007), Çelik (2013) Gallagher ve Stepien (1996), Hmelo Silver (2004), Khoiny (1996) 19 haftalık deneysel çalışma sonunda PDÖ'nin işe koşulduğu deney grubu ile kontrol grubu öğrencilerinin son test öz-düzenleyici öğrenme becerileri ölçeğinden aldıkları puanlar arasında anlamlı bir fark olduğu sonucuna ulaşılmıştır. PDÖ'nin işe koşulduğu deney grubu ile kontrol grubunun son test öz-düzenleyici öğrenme becerileri ölçeğinin "Öğrenme öncesindeki beceriler" boyutuna ilişkin aldıkları puanlar arasında anlamlı bir fark olmadığı görülmüştür.…”
Section: Tartışma Sonuç Ve öNerilerunclassified